Determinan Struktur Modal pada Perusahaan Manufaktur di Bursa Efek Indonesia - Zulvia, Yolandafitri (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2016)
This study examined the effect of asset structure, profitability, growth opportunities and business risks of the company's capital structure. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange (BEI). The sampling technique used purposive sampling and techniques data analysis using regression panel data.These results indicate that the asset structure, profitability, growth opportunities and business risk has a significant negative impact on the capital structure of the company. While the business risk has a not significant positive effect